Deformation and energy absorption characteristics of additively-manufactured polymeric lattice structures — Effects of cell topology and material anisotropy. (December 2021) - Sun, Z.P.; Guo, Y.B.; Shim, V.P.W.
Abstract: Additively manufactured lightweight lattice structures are being widely studied, one aspect being their energy absorption characteristics under large deformation, because their load–deformation responses can be adjusted by specifically tailoring the geometry of constituent cells. In this study, a newly-proposed hybrid structure (HS), which combines the geometrical features of a traditional primarily axial-deformation dominated octet cell and a primarily bending-dominated rhombic dodecahedron (RD), is designed and fabricated via Fused Deposition Modelling. To ascertain whether the geometrical hybrid enhances the energy absorption performance, the quasi-static compressive responses of such lattices are examined and compared with those of the constituent structures, i.e. the octet and RD. It is noted that the layer-wise additive manufacturing process affects the isotropy of the lattices, as it introduces angle-dependent strut material properties. To study this, the mechanical responses of lattice samples compressed along the rise (printing) and transverse directions are compared. Energy absorption efficiency criteria are adopted to identify the onset of the densification phase, and to evaluate how closely they approximate an ideal energy absorber. Finite element models are also established to study the effect of cell topology and loading direction on the resulting deformation modes and failure patterns. Compression tests along the rise direction show that the proposed novel hybrid structure displays a high stiffness and strength comparable to the octet, as well as a relatively stable post-yield stress–strain behaviour similar to that of an RD. The study demonstrates that the octet and HS topologies are significantly affected by the direction of compression, which alters the stress level and changes the deformation mode. The reason for this is analysed by examining deformation at the cell level, and this is substantiated by FE simulation of compression of cell assemblies, and CT scan images of actual lattices. Highlights: Hybrid Structure, geometrical hybrid of octet and RD, to combine their advantage. Anisotropy of lattices induced by layer-wise FDM-based additive manufacturing. Different sensitivity to loading direction associated with lattice cell architecture. Angle-dependent strut material properties used to simulate anisotropy of lattice. Solid element better for modelling lattices with struts of small aspect ratios.